Perancangan Alat Bantu Pemindahan PV Module pada Pemasangan Instalasi PLTS di PT Indonesia Prima Energi - Rasyid Amin; Ganda Sirait (Journal of Innovative and Creativity, 2025)
The study purpose was to design an ergonomic and efficient assistive tool for moving PV Modules during the installation of solar power plants (PLTS) at PT Indonesia Prima Energi to improve work productivity and safety. Materials and methods included problem identification, data collection through direct observation and interviews with workers, literature review, and design using SolidWorks software combined with the Design for Manufacture and Assembly (DFMA) approach. Results showed that the assistive tool reduced the average PV Module handling time from 5.14 minutes to 3.16 minutes per unit, increased productivity by 62%, lowered labor requirements, and significantly decreased operational costs. Conclusions drawn indicate that the designed assistive tool effectively enhances the installation process by speeding up work, improving safety, and supporting sustainable renewable energy development.